2015
DOI: 10.15430/jcp.2015.20.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Deprivation Causes Hydrogen Peroxide-induced Interleukin-8 Expression via Jak1/Stat3 Activation in Gastric Epithelial AGS Cells

Abstract: Background:The Janus kinase (Jak)/Signal transducers of activated transcription (Stat) pathway is an upstream signaling pathway for NF-κB activation in Helicobacter pylori-induced interleukin (IL)-8 production in gastric epithelial AGS cells. H. pylori activates NADPH oxidase and produces hydrogen peroxide, which activates Jak1/Stat3 in AGS cells. Therefore, hydrogen peroxide may be critical for IL-8 production via Jak/Stat activation in gastric epithelial cells. Glutamine is depleted during severe injury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The results from our study suggested the possibility that ROS production was higher in AGS cells infected with GC-derived H. pylori strains, because the decreased degree of GSH level and ratio of GSSG to GSH was greater in the GC-derived strains. A previous report showed that glutamine deficiency decreased the intracellular GSH level and increased the level of hydrogen peroxide, and moreover the GSH treatment cancelled these responses [24]. These results indicates that GSH worked to reduce ROS.…”
Section: Discussionsupporting
confidence: 51%
“…The results from our study suggested the possibility that ROS production was higher in AGS cells infected with GC-derived H. pylori strains, because the decreased degree of GSH level and ratio of GSSG to GSH was greater in the GC-derived strains. A previous report showed that glutamine deficiency decreased the intracellular GSH level and increased the level of hydrogen peroxide, and moreover the GSH treatment cancelled these responses [24]. These results indicates that GSH worked to reduce ROS.…”
Section: Discussionsupporting
confidence: 51%
“…Ouwendijk et al suggested that regulated NETs formation may defend hosts against SARS-CoV-2 infection in asymptomatic or mild cases, but additional factors may lead to excessive NETs production and lung obstruction [ 25 ]. Comorbidity-associated glutamine deficiency may be one of the factors contributing to pathologic NETs production, as glutamine impaired the chemotactic migration of neutrophils to infection sites in an animal model [ 81 ], and glutamine deprivation induced the expression of IL-8 [ 82 , 83 ].…”
Section: Consequences Of Glutamine Deficiency and Covid-19mentioning
confidence: 99%
“…However, as mentioned above, we cannot expect the full restoration of SIRT1 activity by NAD + boosters, as SIRT1 expression is inhibited by SARS-CoV-2 infection. We should also keep in mind that glutamine has been reported as a STAT3 activator in some cancer cell lines [ 84 , 147 ], whereas others found that glutamine has STAT3 inhibiting activity [ 83 , 148 ].…”
Section: Drugs Targeting Stat3mentioning
confidence: 99%
“…Additionally, the production of hydrogen peroxide is encouraged, aggravating the effects of oxidative stress. However, GSH therapy is proved successful in alleviating the high ROS buildup ( 158 ). In conclusion, intestinalization in the gastric host cells is caused by low GSH levels.…”
Section: Potential Oxidative Stress-related Therapeutic Targets In Ga...mentioning
confidence: 99%